The development of public-private partnership as a strategy of modernization of modern Russia - O Y Rodionova (RUDN Journal of Law, 2012)
The article analyses legal approaches to the public private partnership as the form of interaction between public institutions and business, there are outspoken concrete proposals and recommendations related with the perspectives of its development in Russia.